The use of silane-coated industrial glass fibers in splinting periodontally mobile teeth - Amit A Agrawal; Shrikant S Chitko (Wolters Kluwer Medknow Publications, 2011)
In the past, direct stabilization and splinting of teeth using an adhesive technique required the use of wires, pins, or mesh grids. Problems with the current fiber reinforcement materials are their inherent thickness when embedded within composite resin, their availability in fixed widths and their high cost. This paper discusses the use of silane-coated industrial grade glass fibers, which can be bundled in the form of ribbon according to the required thickness and length. Of the three patients discussed in this paper, none has exhibited debonding or recurrent caries over 1-year period. By reinforcing composite splints with these industrial grade glass fibers, dentists can provide patients with restorations and splints that are economical, fracture resistant, and more durable than most alternative splinting materials of the past.